Hydrogen production via thermocatalytic decomposition of methane over Ni-Cu-Pd/Al2O3 catalysts - Awad, A. (Institute of Physics Publishing, 2020)
Non-oxidative decomposition of natural gas is a handsome technique for clean hydrogen production but high reaction temperature and rapid catalyst deactivation limitizes its applications. In current work, decomposition of methane into COX free hydrogen and carbon nanofiber were studied over the bimetallic catalysts. The materials were prepared by wet impregnation method and analyzed by BET, TGA, XRD, FESEM, and TEM. It was observed that with an increase in the metal loading, the surface area was reduced but the methane conversions and catalyst stability were improved since the catalyst activity depend upon the active nickel sites that compensate the surface deficiencies. The highest conversion was given by Ni-Cu-Pd/Al2O3 (80) over a period of 6 h despite having a low BET surface area (2.43 m2 g-1). The physiochemical properties reported that the synthesized catalyst possessed nanostructure and CNF were also produced along with hydrogen as products of TCD. Â© Published under licence by IOP Publishing Ltd.